GENERALIZED SYSTEM RATINGS OF SURFACE OF THE MATERIALS FOR DESIGN OF CLOTHES - Михайлюк, О. Ю.; Колосніченко, М. В.; Остапенко, Н. В.; Гайова, І. Л.; Антонюженко, А. Ю. (Art and Design, 2018)
The purpose of this study is to develop a generalized classification of types of invoices of materials for the manufacture of clothing and other products. In the reserch the complex of general scientific approaches was used: visual-analytical, system-informational and the method of classifications. Findings. On the basis of the conducted researches, existing types of invoices of materials for making clothes and other products are analyzed and summarized. The peculiarities of forming and predicting the perception of tectonically perfect clothes are singled out and disclosed. Originaliti. On the basis of theoretical studies, existing types of invoices of materials for the manufacture of clothes and other products according to different criterias are classified, the methods of their production are systematized. The possibility of predicting the perception of a harmonious artistic and expressive image through the application of textural effects has been proved.